Treatment‐resistant depression as risk factor for substance use disorders—a nation‐wide register‐based cohort study. (15th April 2019) - Brenner, Philip; Brandt, Lena; Li, Gang; DiBernardo, Allitia; Bodén, Robert; Reutfors, Johan
Abstract: Background and aims: Treatment‐resistant depression (TRD) is common among patients with major depressive disorder (MDD). MDD may increase the risk for developing substance use disorders (SUD). The aim of this study was to investigate the risk for developing SUD among patients with TRD compared with other depressed patients. Design: Observational cohort study. Setting: Nation‐wide governmental health registers in Sweden. Participants: All patients aged 18–69 years with an MDD diagnosis in specialized health care who had received at least one antidepressant prescription during 2006–14 were identified. Patients with at least three treatment trials within a single depressive episode were classified with TRD. Measurements: Patients with TRD were compared with the whole MDD cohort regarding risk for obtaining a SUD diagnosis or medication using survival analyses adjusted for socio‐demographics and comorbidities. Findings: Of 121 669 MDD patients, 13% were classified with TRD. Among the patients without any history of SUD, patients with TRD had a risk increase for any SUD both ≤ 1 and > 1 year after antidepressant initiation [> 1 year hazard ratio (HR) = 1.4; 95% confidence interval (CI) = 1.3–1.5]. Risks were elevated for the subcategories of opioid (HR = 1.9, 95% CI = 1.4–2.5) and sedative SUD (HR = 2.7, 95% CI = 2.2–3.2). Patients with a history of SUD had a risk increase for any SUD ≤ 1 year after start of treatment (HR = 1.2, 95% CI = 1.1–1.4), and both ≤ 1 year and > 1 year for sedative (> 1 year HR = 2.0, 95% CI = 1.3–3.0) and multiple substance SUD (HR = 1.9, 95% CI = 1.4–2.5). Conclusions: Patients with treatment‐resistant depression may be at greater risk for substance use disorders compared with other patients with major depressive disorder. Patterns may differ for patients with and without a history of substance use disorders, and for different categories of substance use disorder.